Semeando a cultura audiovisual no Rio Grande do Norte: a experiência das oficinas de vídeos do Coletivo Caminhos, Comunicação & Cultura - Sckaff, Dênia de Fátima Cruz (2014)
The audiovisual media is an instrument of communication that plays an important role in the cultural, social and political understanding of society. This survey was done intenting to identify the contribution of the audiovisual media to the culture in the Rio Grande do Norte and trying to understand the process of producing audiovisual in this state. To reach the aim, a case report was done regard the activities of Caminhos, Comunicação & Cultura – CC&C – a group that conducts cultural activities in the state since 2006 and has 76% of its activities related to audiovisual production, in which 47% of them, are video workshops. The video workshop project "Sowing Culture", held by the group in the city of Venha Ver/RN in January 2013, was observed and analised from its conception to its realization. The research pursued to reveal how the initiatives of independent producers, such as the CC&C group, can promote the access to audiovisual culture in regions where such knowledge is limited or nonexistent, due to the poor state policies related to the culture. Methodologically, the research was structured by performing a historical and descriptive analysis of hypothetical-deductive method through participant observation. For the conceptual and theoretical development, it was addressed the Sociability, Ethnography and media activism. The research proved that the independent audiovisual producers are promoting changes in the RN audiovisual practices. Before the background featured in the research, it is proposed a prognostic from researching to opening the RN Audiovisual Observatory, a communicational tool projected as space of sharing information, thinking, speaking, contacting and promoting the audiovisual productions of the state.